9x^2+12xy+4y^2-24x-16y+3=0
x^2-2xy+y^2-10x-6y+25=0
5x^2+4xy+y^2-6x-2y+2=0
5*x^2+4*x*y+8*y^2+8*x+14*y+5=0
2*x^2+4*y^2+z^2-4*x*y-4*y-2*z+5=0
x^2+y^2-z^2-2*x-2*y+2*z+2=0
x^2+y^2-6*x+6*y-4*z+18=0
x^2+4*y^2+9*z^2+4*x*y+12*y*z+6*x*z-4*x-8*y-12*z+3=0
Equation | Canonical form | Type | Measurement |
---|---|---|---|
9x^2+12xy+4y^2-24x-16y+3=0 | x^2=1 | Two parallel straight lines | Line |
x^2-2xy+y^2-10x-6y+25=0 | y^2=4*sqrt(2)*x | Parabola | Line |
5x^2+4xy+y^2-6x-2y+2=0 | x^2/(1/sqrt(2*sqrt(2)+3))^2 + y^2/(1/sqrt(-2*sqrt(2)+3))^2=0 | Degenerate Ellipse | Line |
5*x^2+4*x*y+8*y^2+8*x+14*y+5=0 | x^2/(3/4)^2+y^2/(1/2)^2=1 | Ellipse | Line |
2*x^2+4*y^2+z^2-4*x*y-4*y-2*z+5=0 | z^2/(2/sqrt(2)/sqrt(3-sqrt(5)))^2+x^2/(2/sqrt(2)/sqrt(3+sqrt(5)))^2+y^2/(2/sqrt(2))^2=-1 | Imaginary Ellipsoid | Surface |
x^2+y^2-z^2-2*x-2*y+2*z+2=0 | x^2/1^2+y^2-z^2=-1 | Double Hyperboloid | Surface |
x^2+y^2-6*x+6*y-4*z+18=0 | x^2/2+y^2-2*z=0 or x^2/2+y^2+2*z=0 | Elliptical Paraboloid | Surface |
x^2+4*y^2+9*z^2+4*x*y+12*y*z+6*x*z-4*x-8*y-12*z+3=0 | x^2/=1/14 | Two Parallel Planes | Surface |